Anti-blast and -impact performances of auxetic structures: A review of structures, materials, methods, and fabrications. (1st February 2023) - Bohara, Rajendra Prasad; Linforth, Steven; Nguyen, Tuan; Ghazlan, Abdallah; Ngo, Tuan
Abstract: Auxetics are a class of structural metamaterials with a negative Poisson's ratio. In comparison to conventional structures, auxetic structures are proven to exhibit several superior properties including higher energy absorption, enhanced indentation resistance, and improved mechanical properties. As a result, auxetic structures are gaining popularity as lightweight, high-performance protective structures to resist blast and impact loads. Although several past reviews on auxetics partially covered different aspects of auxetics, such as classification of architectures, mechanisms, mechanical properties, energy absorption behaviours, and applications, this field still requires a comprehensive overview of the anti-blast and -impact performances of the different auxetic structures. Therefore, this paper aims to review recent advances in auxetic-based lightweight, high-energy absorbing protective structures. Different design factors affecting the performance of the protective structures are critically discussed. Moreover, a classification of modern auxetic topologies, the status of large-scale auxetic fabrication, and anti-ballistic performance evaluation methods are presented in this paper. Overall, auxetic core sandwich panels offer superior protective performance than equivalent conventional protective armours. However, several limitations and challenges exist with the design, fabrication, and implementation of auxetic-based protective structures.